ChemInform Abstract: Photocatalytic Direct Intermolecular Addition of 1, 3‐Dithianes. Issue 10 (February 2016) - Lee, Ming; Chen, Ying‐Ho; Hung, Tzu‐Hang; Chang, Wen; Yan, Wei‐Cheng; Leow, Dasheng
Abstract: The addition of dithianes (I) to various alkenes is accomplished via visible‐light mediated photocatalysis using 23 W 6500 K compact fluorescent light and affords the corresponding disubstituted 1, 3‐dithiane derivatives in good yields.